INTERVENSI PSIKOSOSIAL PENERIMA MANFAAT NAPZA MELALUI PSIKOEDUKASI REGULASI EMOSI DAN KONTROL DIRI - Salsabila Nurul Fatonah; Laila Listiana Ulya; Risye Yulia Triana (FIP UNIRA MALANG, 2026)
Substance abuse involving narcotics, psychotropics, and addictive substances (NAPZA) is a complex issue that affects individuals physically, psychologically, and socially, and increases the risk of relapse. One contributing factor is the lack of emotional regulation and self-control. This study aims to improve emotional regulation and self-control among a beneficiary undergoing substance rehabilitation through psychoeducation and psychosocial assistance. The subject was a 27-year-old male receiving social rehabilitation at Sentra Satria Baturraden. The method included initial assessment, intervention design, implementation of psychoeducation, observation, and evaluation through reflection. The intervention consisted of material delivery, group discussion, question cards, and role play activities, supported by vocational rehabilitation programs as a contextual component in fostering adaptive behavior. The results indicate improvements in the participant’s ability to recognize, understand, and express emotions adaptively, as well as enhanced self-control in dealing with social pressures. Additionally, there were improvements in self-disclosure, social interaction, and motivation to change. These findings suggest that psychoeducation combined with psychosocial assistance using interactive media is effective in supporting the rehabilitation process and reducing relapse risk among individuals with substance use history.